DENTAL IMPLANTATION OSSEOINTEGRATION MECHANISMS: MODERN CONCEPTS AND RESEARCH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The popularity of dental rehabilitation using the dental implantation method determines the interest of researchers in studying the integration of implants in bone tissue. The purpose of this work is to analyze and systematize data from Russian and foreign publications on the problem of osseointegration of titanium implants. An analysis of the literature shows that the improvement of research technologies and an interdisciplinary approach to studying the phenomenon of osseointegration of dental implants in recent years have led to a change in traditional ideas on this problem. Summarizes information about physiological processes and cellular interactions, leaking on the “implant – bone tissue” border at different stages of integration. The results of studies are presented that indicate the need to revise ideas about the bioinertness of titanium implants and consider the integration process from an immunological aspect.